ISOLATION AND IDENTIFICATION OF LIPASE PRODUCING FUNGI FROM THE SOIL ENVIRONMENT OF KEFFI METROPOLIS (FULafia Journal of Science and Technology, 2016)
An investigation was carried out to isolate, identify and screen for lipase producing fungal species present in the soil environment of Keffi metropolis. Soil samples of approximately 200g each were randomly collected from ten different locations within the Keffi metropolis for the investigation. Sabouraud Dextrose Agar was used for the isolation of the fungal species by pour plate method using Direct Soil Inoculation technique. Five fungal species, Acremonium spp, Mucorsp, Rhizopus stolonifer, Aspergillus niger and Aspergillus flavus were isolated and screened for their ability to produce lipases on tween-20 and phenol red agar. The results of lipase production on tween-20 and phenol red after 5 days of incubation showed that all the isolates were positive for lipase production which was indicated by diameter zone of clearance and visible precipitate of calcium monolaurate due to the deposition of calcium crystal. The diameter of the zone of clearance of the various isolates revealed that Rhizopus stolonifer had the highest lipase producing ability (having a diameter zone of clearance of 12 ± 0.04 mm), followed by Aspergillus niger ( having 10 ± 0.02 mm). Acremonium sp. and Mucor sp. had 8 ± 0.07 mm respectively, while Aspergillus flavus was able to produce just a minimal amount of lipases indicated by its zone of clearance (6 ± 0.04mm). These results demonstrate the presence of lipase producing fungi in the soil environment of Keffi metropolis, Nasarawa State, and these can be explored locally for the production of the enzyme which is of value commercially in the production of detergents, and also as constituents of some special diets and pharmaceuticals
Keywords: Lipase production; soil; fungi; Keffi